FRAKSINASI HIDROLISAT PROTEIN BUNGKIL WIJEN (Sesamum indicum L.) SANGRAI MENGGUNAKAN ULTRAFILTRASI DAN SIFAT EMULSINYA - , DEYVIE XYZQUOLYNA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study carried out by enzymatic hydrolysis of roasted sesame cake isolate protein. The enzyme was used a commercial enzyme bromelain. The results obtained were sesame cake protein hydrolysate was then separated based on molecular weight peptide fractions. Protein solubility, HLB value (Hydrophilic/Lipophylic balancae), emulsification properties (emulsion activity index and emulsion stability index) were determined. Fractionation of peptide fractions used by ultrafiltration with membranes Molecular weight cut-off (MWCO) 100, 50, 30, and 10 kDa. The aimed of this study was to determine the effect of time of hydrolysis on the degree of hydrolysis and molecular weight of protein hydrolysates, to determine protein solubility and emulsification properties (emulsion activity index and emulsion stability index) of protein hydrolysates and their fractions. The research consists of 4 stages: preparation roasted sesame cake (defatted flour), preparation roasted sesame cake isolate protein, enzymatic hydrolysis using bromelain. Roasted sesame protein hydrolysate was processed through a series of ultrafiltrations membranes with molecular weight cut-off (MWCO) of 100 , 50, 30 and 10 kDa, and five types of samples including >100 kDa (retentate from 100 kDa), 50-100 kDa (retentate from 50 and permeate 100 kDa), 30-50 kDa (permeate from 50 kDa and retentate from 30 kDa),10-30 kDa (permeate from 30 kDa and retentate from 10 kDa), and <10 kDa hydrolysate (permeate from 10 kDa) were obtained.The degree of hydrolysis, soluble protein, emulsion activity index (EAI), emulsion stability index (ESI) and the HLB value of the protein hydrolyzate were determined. The protein fractions were also analyzed soluble protein, EAI and ESI. The results showed that degree of hydrolysis ranged from 8,09 to 10.52%. Solubility and ESI of the protein hydrolysates, has increased with increase in time of hydrolysis. EAI also increased with increase in time of hydrolysis, but decreased after hydrolysis at 120 minutes. The highest emulsion activity index obtained at 50- 100 kDa peptide fractions after hydrolysis 60 and 90 minutes. After hydrolysis at 90 and 120 minutes the emulsion stability index of the protein hydrolyzate showed an increase.Fractions <10, 10-30 and 30-50 kDa showed excellent emulsion stability index.